seroprevalence of brucellosis and Q fever infections amongst pastoralists and their cattle herds in sokoto state, nigeria (2021)
Brucellosis and Q fever are neglected zoonoses of global health importance, with unknown true prevalence in occupationally vulnerable settings, partly due to misdiagnosis for other febrile conditions and poor access to primary health care. We examined the seroprevalence of these diseases and associated factors amongst pastoralists and their cattle in Sokoto State, a hub of cattle and pastoral populations in Nigeria. Serum samples randomly collected from 137 pastoralists and 366 cattle from 27 herds in three selected Local Government Areas (LGAs) in the state were analysed for antibodies to Brucella abortus using Rose Bengal Plate Test (RBT) and competitive Enzyme-Linked Immunosorbent Assay (cELISA) as well as antibodies to Coxiella burnetti using indirect ELISA. Consenting pastoralists’ knowledge, perception and practices about the diseases were assessed using a semi-structured questionnaire. Data were analysed using descriptive statistics and bivariate analysis at p 0.05 level of significance. Brucellosis adjusted individual seroprevalence were 0.83% (95%CI: 0.04–4.59%) and 0% among pastoralists; 2.28% (95%CI: 1.16–4.43%) and 5.70% (95%CI: 3.68–8.74%) in cattle by RBT and cELISA, respectively. Adjusted herd-level seroprevalence for brucellosis were 23.20% (95%CI: 11.07–42.54%) and 42.00% (95%CI: 25.27–61.11%) by RBT and cELISA, respectively. For Q fever, higher seroprevalence of 62.57% (95%CI: 54.04–70.46%) and 2.98% (95%CI: 1.57–5.58%) were recorded amongst the pastoralists and their cattle, respectively. with adjusted herd-level seroprevalence of 40.36% (95%CI: 22.57–63.17%). The LGAs of sampling were significantly (OR: 0.2; 95%CI: 0.02–1.00) associated with Q fever infection, though marginal. The majority of the pastoralists had poor knowledge, perception and practices towards the diseases. This is the first study establishing the presence of brucellosis and Q fever at the human-animal interface in Sokoto State, Nigeria. The pastoralists’ poor knowledge, perception and practices about these diseases are worrisome and are important factors for consideration in disease control.